Posebnosti digitalizacije arhivskega gradiva in strokovna obravnava tovrstnih digitazitov - Novak, Miroslav (Knjižnica, 2014)
Some special features should be identified when digitizing archival materials. In this regard, the authors highlight the problems of linear and hierarchical sequences of digital copies separated from their original contex, decisions regarding the concepts of digitizing archival materials and the associated metadata provision. Appropriate digitization of archival materials and most of all, appropriate description of digital copies following relevant professional guidelines, facilitates the widespread use of digitized archival content. Digital copies of photos of the Windischgrätz family prove the surprisingly great public interest in some content of archival materials. The case of Windischgrätz family photos and other comparable solution point to the widespread use of digitized archival content, providing good resulth both for users and competent archival institutions.
Keywords: digitalizacija; digitization; archival materials; arhivsko gradivo; digital copies; digitalizati; fotografije; photographies